Stunting Prediction Model in Parepare City - Henni Kumaladewi Hengky; Ayu Dwi Putri Rusman (Sarana Ilmu Indonesia (salnesia), 2022)
One of the big problems regarding nutrition in Indonesia is stunting. A condition known as stunting occurs when a person is shorter than other people. Stunting is caused by a number of things, including malnutrition, a lack of mothers' knowledge about nutrition, a lack of access to health services, a lack of nutritious food, and a lack of clean water and sanitation. The aim of this research was to predict model the incidence of stunting based on the risk factors for children. The cross-sectional design and observational analytical study method were utilized in this research. In the City of Parepare, there are 97 samples of children under the age of five. Interviews, questionnaires, and a length board were used to collect the data. The incidence of stunting was influenced by socioeconomic status (p-value=0,008) and immunization status (p-value=0,032), according to the Chi-square test. According to the results of the multivariate analysis, the most significant determinant of the prevalence of stunting in Parepare City was socioeconomic status.